Analisis Potensi Produk Olahan Pertanian Berbasis Pangan Lokal oleh UMKM: Studi Kasus Coklat Raddina Jember - Hikmah, Faiqotul; Nasilah, Rohmatun; Efendi, Mohammad Lukman; Firmansyah, Moh. Irsyad; Irfansah, Candra; Putra, Mohammad Aldi Eka; Isnaini, Muhammad Fadjar; Putra, Muhammad Rizki Hafianto; Muzayyin, Muzayyin (Journal of Health, Education, Economics, Science, and Technology, 2025)
This study analyzes the potential of agricultural processed products based on local food developed by the MSME Cokelat Raddina in Jember Regency. The research employs a qualitative descriptive method with a single case study approach. Data were collected through interviews, observations, and documentation, then analyzed using the Miles and Huberman model. Results show the MSME utilizes local cocoa as the main ingredient and develops innovative products such as spicy chocolate and shredded chocolate. Branding strategies and digital marketing through Instagram and TikTok are key to promotion. The SWOT analysis reveals strengths in raw materials and innovation, weaknesses in capital access and digital marketing, opportunities from growing demand for local products, and threats from price fluctuations and import competition. The study concludes that optimizing local food programs and product innovation can enhance the competitiveness and sustainability of MSMEs in the region.